Biobutanol Production in a Mixed Culture System of Clostridium Acteobutylicum ATCC 824 and Bacillus Subtilis DSM 4451 - N. Nor, Azaini; N., Masngut (2015)
In this study, the mix culture system consists of anaerobic Clostridium acetobutylicum and aerobic Bacillus subtilis was used to develop an anaerobic condition in the fermentation. B. subtilis consumed oxygen in the broth and maintaining anaerobic condition for C. acetobutylicum to grow. Hence, the culture was maintained in anaerobic condition without the use of N2 gas. Comparison between pure culture fermentation of C. acetobutylicum (control) with the mixed culture was carried out. The parameter studied was the inoculum ratio of C. acetobutylicum to the B. subtilis in the mixed culture fermentation which are 1:1, 1:2, 1:3, 2:1 and 3:1. The result shows that ratio of 1:3 mixed culture produced the highest butanol with 0.25 g/L which is almost twice than that in control fermentation. Hence, it shows that the butanol can be produced from mixed culture of C. acetobutylicum and B. subtilis.